Parents' early representations of their children moderate socialization processes: Evidence from two studies. (21st August 2022) - An, Danming; Kochanska, Grazyna
Abstract: Difficult infants are commonly considered at risk for maladaptive developmental cascades, but evidence is mixed, prompting efforts to elucidate moderators of effects of difficulty. We examined features of parents' representations of their infants – adaptive (appropriate mind-mindedness, MM) and dysfunctional (low reflective functioning, RF, hostile attributions) – as potential moderators. In Family Study ( N = 102), we tested parents' appropriate MM comments to their infants as moderating a path from infants' observed difficulty (negative affect, unresponsiveness) to parents' observed power assertion at ages 2–4.5 to children's observed and parent-rated (dis)regard for conduct rules at age 5.5. In father–child relationships, MM moderated that path: for fathers with low MM, the infants' increasing difficulty was associated with fathers' greater power assertion, which in turn was associated with children's more disregard for rules. The path was absent for fathers with average or high MM. In Children and Parents Study ( N = 200), dysfunctional representations (low RF, hostile attributions) moderated the link between child objective difficulty, observed as anger in laboratory episodes, and difficulty as described by the parent. Reports of mothers with highly dysfunctional representations were unrelated to children's observed anger. Reports of mothers with average or low dysfunctional representations aligned with laboratory observations.